Ropivacaine- and bupivacaine-induced death of rabbit annulus fibrosus cells in vitro: involvement of the mitochondrial apoptotic pathway. Issue 10 (October 2015) - Cai, X.-Y.; Xia, Y.; Yang, S.-H.; Liu, X.-Z.; Shao, Z.-W.; Liu, Y.-L.; Yang, W.; Xiong, L.-M.
Summary: Objective: The purposes of this study were to assess whether local anesthetics (LAs), such as ropivacaine and bupivacaine, could induce apoptosis of rabbit annulus fibrosus (AF) cells in vitro and further to explore the possible underlying mechanism. Methods: Rabbit AF cells at second passage were treated with saline solution and various concentrations of LAs. Apoptosis of AF cells were examined by cell counting kit-8 (CCK-8), Annexin V assays, Hoechst 33342 staining, and Caspase-3, -9 activity assays. The expression of apoptosis-related markers was detected by real-time PCR (RT-PCR) and Western Blot. The JC-1 staining was used to evaluate the change of mitochondrial membrane potential (MMP). Moreover, the levels of reactive oxygen species (ROS) were determined with fluorescent probe DCFH-DA. Results: The results of flow cytometry indicated that LAs could induce apoptosis of rabbit AF cells in a dose-dependent manner. Apoptosis was confirmed by cell morphology, condensed nuclei and activation of Caspase-3 and -9. In addition, the molecular data showed that LAs could significantly up-regulate the expression of Bax, accompanied by a significant down-regulation of Bcl-2 expression. Furthermore, we also observed that LAs resulted in alteration of MMP and accumulation of intracellular ROS in AF cells. Blockade of ROS production by N-acetyl-l -cysteine (NAC) inhibited LAs-induced apoptosis. Conclusions: These findings suggest that LAs in clinically relevant concentrations could induce apoptosis of rabbit AF cells in vitro, and the mitochondrial pathway was, at least in part, involved in the LAs-mediated apoptosis. Further investigations focusing on the potential cytotoxicity of LAs on IVD cells are needed.